Copper-Induced Increased Expression of Genes Involved in Photosynthesis, Carotenoid Synthesis and C Assimilation in the Marine Alga Ulva Compressa - Garcia Huidobro-Toro, J; Moenne-Munoz, A; Laporte-Poblete, D; Rodriguez-Tirado, F; Gonzalez-Figueroa, A (BioMed Central Ltd., 2018)
Background: The marine alga Ulva compressa is the dominant species in coastal areas receiving effluents from copper mines. The alga can accumulate high amounts of copper and possesses a strong antioxidant system. Here, we performed short-term transcriptomic analyses using total RNA of the alga cultivated with 10 μM of copper for 0, 3, 6, 12 and 24 h by RNA-seq. Results: De novo transcriptomes were assembled using the Trinity software, putative proteins were annotated and classified using Blast2GO. Differentially expressed transcripts were identified using edgeR. Transcript levels were compared by paired times 0 vs 3, 0 vs 6, 0 vs 12 and 0 vs 24 h at an FDR < 0.01 and Log2 Fold Change > 2. Up-regulated transcripts encode proteins belonging to photosystem II (PSII), Light Harvesting II Complex (LHCII), PSI and LHCI, proteins involved in assembly and repair of PSII, and assembly and protection of PSI. In addition, transcripts encoding enzymes leading to β-carotene synthesis and enzymes belonging to the Calvin-Benson cycle were also increased. We further analyzed photosynthesis and carotenoid levels in the alga cultivated with 10 μM of copper for 0 to 24 h. Photosynthesis was increased from 3 to 24 h as well as the level of total carotenoids. The increase in transcripts encoding enzymes of the Calvin-Benson cycle suggests that C assimilation may also be increased. Conclusions: Thus, U. compressa displays a short-term response to copper stress enhancing the expression of genes encoding proteins involved in photosynthesis, enzymes involved carotenoids synthesis, as well as those belonging to the Calvin-Benson cycle, which may result in an increase in C assimilation. © 2018 The Author(s).